Can I Trust My Phone to Replace My Wallet? The Determinants of E-Wallet Adoption in North Cyprus - Kinis, Fatma; Tanova, Cem (Mdpi, 2022)
E-wallets and mobile payment systems provide fast, secure, and convenient payment in transactions services while minimizing the need for human interaction. However, the adoption of the technology has had varying levels of success. Using a sample of 300 respondents, the study randomly assigned participants into three conditions and provided different information on how they would be reimbursed by their bank in case of fraud. In the three conditions, this study analyzed how prior consumer knowledge about e-wallet technology along with perceived usefulness, perceived ease of use, and trust may be related to the attitudes on the use of e-wallets, which subsequently relates to the intentions to use this technology. The findings suggest that consumer knowledge about e-wallet technology relates to perceived usefulness, perceived ease of use, and trust, which are known to influence attitude and behavioral intention to adopt and use new technologies such as the e-wallet. In addition, the results displayed that those respondents who were assured of immediate reimbursement in case of fraud may have higher intention to adopt e-wallets when compared to those who were informed of delayed reimbursement or those given no information. While the ANOVA results provided tentative support for the hypothesis that assurance of reimbursement will improve the intention to use e-wallet, the subsequent ANCOVA findings demonstrate that when prior consumer knowledge is taken into consideration and groups are compared with this factor in the equation, the group differences disappear.
Keywords: technology acceptance model; e-wallet; mobile payment